Synthesis of bimetallic Ag-Cu nanoparticles using chemical reduction method as antibacterial agents against Escherichia coli - Ceria Sitorus; Makmur Sirait; Rita Juliani; Motlan Motlan; Eva Marlina Ginting; Nurdin Siregar; Rafles Sinaga (Universitas Sebelas Maret, 2025)
Bimetallic nanoparticles offer enhanced antibacterial properties due to synergistic effects between different metal ions. In this study, Ag-Cu nanoparticles were synthesized using a chemical reduction method with NaBH₄ as the reducing agent and PVP as a stabilizer. The resulting nanoparticles showed a greenish-black color and an average particle size of 308.8 nm with narrow distribution. Antibacterial activity against Escherichia coli was tested using the disc diffusion method at concentrations of 5%, 10%, and 15%. The results showed a concentration-dependent increase in inhibition zones, with a maximum average of 7.8 mm. Although lower than the positive control, the findings confirm the potential of Ag-Cu nanoparticles as alternative antibacterial agents. Further optimization is recommended for biomedical applications.